2017
DOI: 10.1016/j.ajog.2016.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician call schedule and obstetric outcomes among women eligible for a trial of labor after cesarean

Abstract: BACKGROUND Reducing cesarean deliveries is a major public health goal. The low rate of vaginal birth after cesarean (VBAC) has been attributed largely to a decrease in likelihood of choosing a trial of labor after cesarean (TOLAC), despite evidence suggesting a majority of women with one prior low transverse cesarean are TOLAC candidates. While a number of reasons for this decrease have been explored, it remains unclear how systems issues such as physician call schedules influence delivery approach and mode in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Guidelines recommend that the final decision to undergo TOLAC should be made through shared decision‐making by the woman in consultation with her obstetrician . It stands to reason, supported by growing evidence, that obstetricians can easily influence women's decisions . Obstetricians, in turn, will be influenced by factors related to the healthcare system, institutional and organisational factors, and litigation .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Guidelines recommend that the final decision to undergo TOLAC should be made through shared decision‐making by the woman in consultation with her obstetrician . It stands to reason, supported by growing evidence, that obstetricians can easily influence women's decisions . Obstetricians, in turn, will be influenced by factors related to the healthcare system, institutional and organisational factors, and litigation .…”
Section: Discussionmentioning
confidence: 85%
“…Healthcare providers can contribute to lower TOLAC rates by providing higher reimbursement for CSs compared with vaginal deliveries. Yee et al identified a more than two‐fold increase in the likelihood of attempting TOLAC, with a similar increase in VBAC, in a night float call system (schedule in which the provider has clinical responsibilities for labouring women only for a day or night shift) compared with a traditional call system . Obstetricians working in institutions with obstetric, paediatric, anaesthetic and operating room staff immediately available might be more likely to offer TOLAC.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…(Munro et al, 2017) Associations between quality of care and lack of resources have previously been described, such as lack of a local NICU resulting in low birth weight infants born at hospitals without a NICU and physician call schedules associated with use of TOLAC. (Kozhimannil, Hung, Casey, & Lorch, 2016;Yee et al, 2017).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…(Edmonds, O'Hara, Clarke, & Shah, 2017;Jolles, 2017;Plough et al, 2017;Prasad, Hung, Henning-Smith, Casey, & Kozhimannil, 2018;Sebastiao et al, 2016) Additional characteristics that vary by hospital, such as physician workload and access to hospital surgical resources, are associated with access to Trial of Labor after Cesarean (TOLAC). (Munro et al, 2017;Yee, Liu, & Grobman, 2017) It is not yet known how geographic characteristics of the county of maternal residence contribute to these hospital variations.…”
Section: Introductionmentioning
confidence: 99%